2012
DOI: 10.1111/j.1523-5378.2012.00947.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonbismuth Quadruple (Concomitant) Therapy: Empirical and Tailored Efficacy versus Standard Triple Therapy for Clarithromycin‐Susceptible Helicobacter pylori and versus Sequential Therapy for Clarithromycin‐Resistant Strains

Abstract: Empirical 10-day concomitant therapy achieves good eradication rates, close to 90%, in settings with multiresistant H. pylori strains. Tailored concomitant therapy is significantly superior to triple therapy for clarithromycin-susceptible H. pylori and at least as effective as sequential therapy for resistant strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 36 publications
(51 reference statements)
7
37
2
Order By: Relevance
“…11 More recently, multiple trials of concomitant NBQT have confirmed an ITT eradication rate of 75-96.4% (per-protocol rates consistently superior to 80%) with a possible advantage for longer treatment duration (Table 3). 15,16,[21][22][23][24][25][26][27][28][29][30][31][32] The results of this randomized trial appear to confirm our earlier observation 13 that reduced-dose regimens (down to 50% posology) performs similarly to standard-dose regimens with the added benefit of reduced cost and adverse events. To date, three randomized controlled trials, involving a total of 475 patients, have examined the value of 50% reduction in the dose of all administered antibiotics for H. pylori (two STT and the current concomitant NBQT) and have all confirmed similar eradication rates to the standard-dose comparator (Table 4), with a reduction in adverse events and cost.…”
Section: Discussionsupporting
confidence: 80%
“…11 More recently, multiple trials of concomitant NBQT have confirmed an ITT eradication rate of 75-96.4% (per-protocol rates consistently superior to 80%) with a possible advantage for longer treatment duration (Table 3). 15,16,[21][22][23][24][25][26][27][28][29][30][31][32] The results of this randomized trial appear to confirm our earlier observation 13 that reduced-dose regimens (down to 50% posology) performs similarly to standard-dose regimens with the added benefit of reduced cost and adverse events. To date, three randomized controlled trials, involving a total of 475 patients, have examined the value of 50% reduction in the dose of all administered antibiotics for H. pylori (two STT and the current concomitant NBQT) and have all confirmed similar eradication rates to the standard-dose comparator (Table 4), with a reduction in adverse events and cost.…”
Section: Discussionsupporting
confidence: 80%
“…Recently, several studies have compared concomitant therapy to STT and sequential therapy. In one study, 10-d concomitant therapy resulted in a better eradication rate in settings with antibiotic-resistant H. pylori strains [97] . Eradication rates for concomitant and sequential therapies were 100% vs 75% for clarithromycin-resistant strains and 75% vs 60% for clarithromycin-resistant/metronidazoleresistant strains [97] .…”
Section: Are There Suitable Sequential and Concomitant Therapy Alternmentioning
confidence: 99%
“…In one study, 10-d concomitant therapy resulted in a better eradication rate in settings with antibiotic-resistant H. pylori strains [97] . Eradication rates for concomitant and sequential therapies were 100% vs 75% for clarithromycin-resistant strains and 75% vs 60% for clarithromycin-resistant/metronidazoleresistant strains [97] . A meta-analysis of 15 studies showed a mean H. pylori eradication rate of 90% by ITT analysis for concomitant therapy and reported that longer treatment improved the outcomes compared to STT [98] .…”
Section: Are There Suitable Sequential and Concomitant Therapy Alternmentioning
confidence: 99%
“…It was successful in several trials and especially on clarithromycin resistant strains in a Spanish trial. 60 A review of this therapy involving 2070 patients from 19 studies obtained a mean eradication rate of 88%. 61 There are also some attempts to combine the 2 approaches, sequential and concomitant, by prescribing a 14-d sequential regimen but continuing amoxicillin during the entire period, the so-called hybrid therapy.…”
Section: Sequential or Concomitant Non-bismuth Quadruple Therapiesmentioning
confidence: 99%